Effect of some morphological characteristics and chemical resistant maize corn borer stalk - Baghdad Science Journal (مجلة بغداد للعلوم, 2006)
There significant correlation between vehicles Home (carbohydrates, protein, fiber and fat and injury borer stalk corn was for vehicles secondary effect is clear in injury borer stalk corn coumarin clear impact in the survival rate of larvae The more of these compounds in genotype I survival rate of larvae